Nasally administered Lactobacillus rhamnosus strains differentially modulate respiratory antiviral immune responses and induce protection against respiratory syncytial virus infection - Tomosada, Yohsuke (2013)
Some studies have shown that nasally administered immunobiotics had the potential to improve the outcome of influenza virus infection. However, the capacity of immunobiotics to improve protection against respiratory syncytial virus (RSV) infection was not investigated before. Objective: the aims of this study were: a) to evaluate whether the nasal administration of Lactobacillus rhamnosus CRL1505 (Lr05) and L. rhamnosus CRL1506 (Lr06) are able to improve respiratory antiviral defenses and beneficially modulate the immune response triggered by TLR3/RIG-I activation; b) to investigate whether viability of Lr05 or Lr06 is indispensable to modulate respiratory immunity and; c) to evaluate the capacity of Lr05 and Lr06 to improve the resistance of infant mice against RSV infection. Results: nasally administered Lr05 and Lr06 differentially modulated the TLR3/RIG-I-triggered antiviral respiratory immune response. Lr06 administration significantly modulated the production of IFN-α, IFN-β and IL-6 in the response to poly(I:C) challenge, while nasal priming with Lr05 was more effective to improve levels of IFN-γ and IL-10. Both viable Lr05 and Lr06 strains increased the resistance of infant mice to RSV infection while only heat-killed Lr05 showed a protective effect similar to those observed with viable strains. Conclusions: the present work demonstrated that nasal administration of immunobiotics is able to beneficially modulate the immune response triggered by TLR3/RIG-I activation in the respiratory tract and to increase the resistance of mice to the challenge with RSV. Comparative studies using two Lactobacillus rhamnosus strains of the same origin and with similar technological properties showed that each strain has an specific immunoregulatory effect in the respiratory tract and that they differentially modulate the immune response after poly(I:C) or RSV challenges, conferring different degree of protection and using distinct immune mechanisms. We also demonstrated in this work that it is possible to beneficially modulate the respiratory defenses against RSV by using heat-killed immunobiotics.